“Pęknięcie historii” (The Split of History). Christiane Hoffmann’s Alles, was wir nicht erinnern Against the Background of Cultural Narratives About “Escapes and Expulsions” - Stankowska, Agata (Porównania, 2025)
This article is about the book Alles, was wir nicht erinnern. Zu Fuß auf dem Fluchtweg meines Vaters by Christiane Hoffmann. The author considers this work in the field of genological references. She focuses primarily on deciphering the historical vision presented by Hoffmann in her literary reportage. The author reveals the tension between the anthropological approach to the story told and the mythologizing efforts. The latter serve to perpetuate cultural narratives about the “escape and expulsion” of Germans at the end of World War II and very clearly repeat the patterns characteristic of collective memory and the politics of memory in contemporary Germany.